2020
DOI: 10.1063/1.5124681
|View full text |Cite
|
Sign up to set email alerts
|

Design and performance of a superconducting neutron resonance spin flipper

Abstract: Despite the challenges, neutron resonance spin echo still holds the promise to improve upon neutron spin echo for the measurement of slow dynamics in materials. We present a bootstrap, radio frequency neutron spin flipper using high temperature superconducting technology capable of flipping neutron spin with either nonadiabatic or adiabatic modes. A frequency of 2 MHz has been achieved, which would achieve an effective field integral of 0.35 T m for a meter of separation in a neutron resonance spin echo spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…With this approach, the resolution function of MIEZE can be modified such that the contrast of the intensity modulation can be maximized at any scattering angle of interest. In contrast to the approach of rotating the RF flippers (Dadisman et al, 2022), the approach with MWPs can shape the wavefront at the sample position precisely such that the correction efficiency is independent of the beam divergence and neutron wavelength. Such a correction approach with MWPs will be demonstrated in a future experiment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…With this approach, the resolution function of MIEZE can be modified such that the contrast of the intensity modulation can be maximized at any scattering angle of interest. In contrast to the approach of rotating the RF flippers (Dadisman et al, 2022), the approach with MWPs can shape the wavefront at the sample position precisely such that the correction efficiency is independent of the beam divergence and neutron wavelength. Such a correction approach with MWPs will be demonstrated in a future experiment.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach to allow for the complicated sample environment that involves high magnetic field and depolarizing sample is to use modulation of intensity emerging from zero effort (MIEZE) (Ga ¨hler et al, 1992), which has been demonstrated or routinely operated at several neutron facilities, including Larmor at ISIS (Geerits et al, 2019), ORNL (Brandl et al, 2012;Dadisman et al, 2020;Zhao et al, 2015), CMRR (Liu et al, 2020), RESEDA of FRM-II and VIN ROSE at J-PARC (Hino et al, 2013). Depending on the direction of the static magnetic field inside the radio-frequency (RF) flippers with respect to the beam, there are longitudinal and transverse configurations for MIEZE.…”
Section: Mieze and Its Larmor Phase Aberrationmentioning
confidence: 99%
See 2 more Smart Citations
“…It is routinely available at the spectrometer RESEDA at the Heinz Maier-Leibnitz Zentrum (Franz & Schro ¨der, 2015) and BL06 at the J-PARC Materials and Life Science Experimental Facility (Kawabata et al, 2006;Hino et al, 2013). Furthermore, MIEZE is being actively developed at the Reactor Institute Delft, the ISIS neutron source (Geerits et al, 2019) and Oak Ridge National Laboratory (Dadisman et al, 2020). In Fig.…”
Section: Introductionmentioning
confidence: 99%